Taksonomiczna analiza fundamentalna jako element systemu wspomagania decyzji inwestycyjnych i lokacyjnych - Lewandowski, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this article author proposed an alternative approach to the classical fundamental analysis. This approach is based on using taxonomic methods to build a system helping financial analyst to initially identify a company with high growth potential in the particular branch of economy. The element of mentioned system, taxonomic, situational analysis, was presented in details. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 352-362